Specific fracture energy for normal strength concrete, high strength concrete and fibre reinforced concrete - three approaches - Karthick, B.; Muthuraj, M.P. (Journal of Structural Engineering, 2024)
For the analysis of cracked concrete structures, advanced mechanical properties, such as fracture energy and thecorresponding tension softening relation are essential. Although significant studies have been reported on evaluationof specific fracture energy, still, there is no clarity and applicability of the approach for various concretes. This paperexamines the determination of fracture energy by using (i) RILEM work of fracture with tail correction to loaddisplacementplot (ii) boundary effect model of Hu and Wittmann and (iii) energy release rate approach for variousconcrete mixes. Several concrete mixes, whose compressive strength ranges from about 20 to 90 MPa comprising ofnormal strength concrete, high strength concrete and fibre reinforced concrete have been considered in the presentstudy to evaluate the specific fracture energy. From the study, it is observed that the specific fracture energy obtainedby the above methods are in close agreement with each other and designer can employ either of the methods foranalysis and design of concrete structures and also for safety evaluation of sensitive structures.